The review of Butana and Kenana breeds - Osman, A.H. (1983)
Reviews breed characteristics of Kenana and Butana cattle in Sudan. Discussions on physical, production and reproduction characteristics including horns, hump, umbilical fold, size and growth, fertility, milk yield, meat production; and production systems included.